Proposed methodology for research into the socioecological resilience of agroecosystems (2015)
ABSTRACT: Agroecology proposes a new epistemological and methodological paradigm to understand the reality of farming and livestock production systems that are in turn nature-society systems. The research questions around these have traditionally been resolved from two methodological approaches: quantitative and qualitative. Although each complements the other, there have not been sufficient approximations from a perspective that would integrate them. A holistic, transdisciplinary agroecological proposal should transcend the theoretical discourse and become practical trough research aiming to understand the socio-ecological relationships in the agroecosystems, report the complex phenomena arising from such relationships and prepared detailed diagnostics from a systemic point of view. Reflections are presented here on the traditional methodological approaches to agroecology and new proposals that respond to the epistemological approach of the agroecological discourse.